1977
DOI: 10.1017/s0021859600033979
|View full text |Cite
|
Sign up to set email alerts
|

Thein vitrodigested cell wall and fermentation characteristics of grasses as affected by temperature and humidity during their growth

Abstract: Total cell wall, in vitro digested cell wall and fermentation-gas production were determined in the separated tops and stubble of five tropical and two temperate grass species grown under controlled temperatures and humidities. As the day/night temperatures increased from 18/10 to 25/17 C C the total cell wall and in vitro digested cell wall increased. With a further increase to 32/24 °C the total cell wall increased, but not the in vitro digested cell wall. In vitro digested cell-wall values were also calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This helps to explain the minimal change in DMD of the tropical species with temperature in the current experimental material (Wilson and Ford 1973) even though the cell wall content decreased, and the steeper fall in DMD at high temperatures compared with cell wall levels , associated with a decreased digestibility of the cell wall (Moir et al 1977).…”
Section: Discussionmentioning
confidence: 64%
“…This helps to explain the minimal change in DMD of the tropical species with temperature in the current experimental material (Wilson and Ford 1973) even though the cell wall content decreased, and the steeper fall in DMD at high temperatures compared with cell wall levels , associated with a decreased digestibility of the cell wall (Moir et al 1977).…”
Section: Discussionmentioning
confidence: 64%
“…Previous controlled-environment studies have investigated the effects of separate environmental influences on various quality indices of tropical and temperate grasses (2,4,5,6,7,8,10,13,16,17,18,20,21). Wilson and Minson (19) recently reviewed many of these relationships as they apply to tropical grasses.…”
mentioning
confidence: 99%
“…Fales et a6 (1981) demonstrated that the xylose content of tall fescue increased in late spring and decreased in late summer, and attributed the variation in hemicellulose content to photoperiod length. The cell wall digestibility of both cool-and warm-season grasses decreases as temperature increases Dirven 1971, 1976;Moir et al 1977), and digestibility is further reduced by ageing (Deinum and Dirven 1975;Wilson 1976). Levels of p-coumaric ($A) and ferulic (FA) acids (Akin et al 1987), and of indigestible neutral detergent fibre (NDF) (Fales 1986) increase with temperature in tall fescue, suggesting that, at least in cool-season grasses, an increase in lignification contributes to the decrease in cell wall digestibility.…”
Section: Regrowthmentioning
confidence: 99%